Altered Macular Microvasculature in Mild Cognitive Impairment and Alzheimer Disease. Issue 3 (September 2018) - Jiang, Hong; Wei, Yantao; Shi, Yingying; Wright, Clinton B.; Sun, Xiaoyan; Gregori, Giovanni; Zheng, Fang; Vanner, Elizabeth A.; Lam, Byron L.; Rundek, Tatjana; Wang, Jianhua
Abstract : Background: The goal of the present study was to analyze the macular microvacular network in mild cognitive impirment (MCI) and Alzheimer disease (AD). Methods: Twelve patients with AD and 19 patients with MCI were recruited together with 21 cognitively normal controls with a similar range of ages. Optical coherence tomography angiography was used to image the retinal microvascular network at the macular region, including retinal vascular network (RVN), superficial vascular plexus (SVP), and deep vascular plexus (DVP). Fractal analysis (box counting, Dbox ) representing the microvascular density was performed in different annular zones and quadrantal sectors. The macular ganglion cell–inner plexiform layer (GC-IPL) thickness was measured using Zeiss OCT. The relationship between the retinal microvasculature and clinical manifestations was analyzed. Results: Patients with AD had lower densities of RVN, SVP, and DVP in the annulus, from 0.6 to 2.5 mm in diameter ( P < 0.05) in comparison with controls. Patients with MCI had lower density of DVP in the superior nasal quadrant ( P < 0.05) than that of the controls. There were no significant differences of GC-IPL thickness among groups ( P > 0.05). There was a trend of vascular density loss from control to MCI then AD ( P < 0.05). Retinal microvascular density of DVP was correlated with GC-IPL thickness ( P < 0.05) in patients with AD, but not in patients with MCI and controls. Conclusions: Patients with AD had less density of retinal microvascular networks than controls. Our findings suggest the presence of retinal microvascular dysfunction in AD. Abstract : Supplemental Digital Content is Available in the Text.